O problema do caixeiro viajante com múltiplos passageiros e quota - Carvalho, Allan Vilar de (2018)
The present work presents the Traveling Salesman Problem with Multiple Passengers and Quota, variant of the Traveling Salesman Problem with Quota. The problem is to minimize the costs of a salesman who must collect a minimum quota of bonuses in the localities of the problem, considering the possibility of apportionment of expenses for any passengers on the route with embedded vehicle traveling. Passengers, if shipped, must be transported obligatorily to their destinations previously known. Passengers participate in the apportionment of the costs of the route in excerpts in which you sail. The paper proposes and validates a Linear Mathematical Programming model to formalize the problem. Are proposed also a bank of instances and heuristics for solving the problem. Computational experiments validate the proposed methods through the solution of the instances of the proposed bank. Developing a computational experiment to obtain conclusions about the efficiency and effectiveness of the proposed methods.